2021
DOI: 10.1136/gpsych-2020-100289
|View full text |Cite
|
Sign up to set email alerts
|

Safety and related factors of treatment with long-term atypical antipsychotic in Chinese patients with schizophrenia: observational study

Abstract: BackgroundAtypical antipsychotics as first-line drugs have been used in patients with schizophrenia in China and abroad. However, its safety still needs to be evaluated in a large population, especially in Chinese patients.ObjectiveThe main objective of this study is to evaluate the safety and related factors of long-term atypical antipsychotic use in patients with schizophrenia in China. The secondary objective includes the long-term efficacy of atypical antipsychotics in these patients, as well as pharmacoec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The patients of the present study were collected from An Observational Study on Atypical Antipsychotics Long-term Treatment Patients with Schizophrenia (SALT-C), a large sample, non-interventional and long-term prospective clinical study in China ( 15 ). The study was approved by the Institutional Review Board of Shanghai Mental Health Center, with the number of 2010-35, 2016-23.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients of the present study were collected from An Observational Study on Atypical Antipsychotics Long-term Treatment Patients with Schizophrenia (SALT-C), a large sample, non-interventional and long-term prospective clinical study in China ( 15 ). The study was approved by the Institutional Review Board of Shanghai Mental Health Center, with the number of 2010-35, 2016-23.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 842 SCZ patients were recruited for the SALT-C(15). After careful screening, 34 SCZ patients were enrolled in the present study eventually, covering SCZ patients with cognitive impairment (n = 17, it was shown that MoCA < 26 at both time points, group CI), and SCZ patients with cognitive normal (n = 17, MoCA ≥ 26 at both time points, group CN).…”
mentioning
confidence: 99%
“…After that, the data was put through a normal distribution test. The composition ratio should characterize the count data if the data has a normal distribution, and the differences between groups were explored using the chi-square test [11][12][13]. The measurement data should be expressed as (mean standard deviation), the t test should be used to examine the differences between groups, and the physical influencing factors of the case group should be investigated using Logistic regression P0:05 is considered statistically significant.…”
Section: The Observation Indexmentioning
confidence: 99%
“…The study was based on a real-world multicenter clinical trial called An Observational Study on Atypical Antipsychotics Long-term Treatment Patients with Schizophrenia (the SALT-C Study). The protocol of this trial was approved by the Ethics Committee of Shanghai Mental Health Center and assigned to the International Clinical Trials Registry Platform number NCT02640911 10 …”
Section: Methodsmentioning
confidence: 99%